Dosis de gallinaza y sus efectos en los componentes agronómicos y rendimiento de Vigna unguiculata L. subsp. Sesquipedalis chiclayo verdura, en un suelo frando arenoso, Zungarococha - Loreto.2022 unguiculata - Iruyari Panduro, Nair (2022)
The experiment "Doses of gallinaza and its effects on the agronomic components and yield of Vigna unguiculata L. subsp sesquipedalis Chiclayo vegetable, in a Sandy Loam soil, Zungarococha-Loreto.2022" was developed in the Workshop of Teaching and Research of Horticultural Plants of the Faculty of Agronomy-UNAP, south of the city of Iquitos. The type of research was experimental explanatory, quantitative, prospective and cross-sectional with an independent variable (chicken dose) and six dependent variables (plant height, pod length, number of pods/plants, pod weight, pod/plant weight and pod weight/ha. The overall goal was. to assess the effects of chicken doses on agronomic components and yield de Vigna unguiculata L. subsp sesquipedalis Chiclayo verdura, en un suelo Franco Arenoso, Zungarococha-Loreto.2022 El Diseño estadístico empleado fue el Diseño de Bloques Completamente al Azar (DBCA), con cuatro tratamientos y cuatro repeticiones. Los Tratamientos estudiados fueron: .T1: 30 t de gallinaza/ha; T2: 40 t de gallinaza/ha; T3: 50 t de gallinaza/ha y T4: 60 t de gallinaza/ha. At the end of the experiment, the following conclusions were reached: The doses of gallinaza significantly influenced the results of the agronomic characteristics and yield of the crop of Vigna unguiculata L. subsp sesquipedalis Chiclayo vegetable, in a Sandy Loam soil, Zungarococha-Loreto; the T4 Treatment (60 t of chicken /ha), presented the best agronomic characteristics of plant height (210 cm), length of pod (70 cm) and better yields of sheath weight (38 g), number of pods / plant (25 units), weight of pods / plant (954 g) and weight of pods / ha (19,080 Kg) and also, presented the best economic income with S/. 42,940.00